Spatial Distribution and Suitability of the Endemic Babirusa Habitat (Babyrousa babyrussa) on Buru Island, Maluku using Maximum Entropy - Heinrich Rakuasa; Vadim V Khromykh; Philia Christi Latue; Susan E Manakane; Glendy Somae; Benson Joshua (Program Studi Pendidikan Biologi FKIP Unpatti, 2026)
Buru Island is the endemic habitat of the Babirusa (Babyrousa babyrussa), facing pressures from human activities and habitat fragmentation. This study used the Maximum Entropy (MaxEnt) modeling method to map the spatial distribution and assess the habitat suitability of Babirusa based on environmental variables including elevation, slope, temperature, land cover, distance to water, and distance from built-up areas. The results show that the habitat is divided into four main classes: Very Low at 24.95%, Low at 31.67%, Moderate at 29.71%, and High at 13.68% of the total island area, which requires more intensive management and protection. Elevation and distance from settlements have an influence but with relatively small contributions, indicating the species’ tolerance to elevation variation. This model provides a scientific basis for integrated conservation strategies, including habitat management, reduction of anthropogenic pressures, and sustainable spatial planning based on habitat suitability to ensure the long-term survival of Babirusa on Buru Island.